PENGARUH PENERAPAN MODEL PEMBELAJARAN PROBLEM SOLVING TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA - Yanti, Elza Fitri; Adripen, Adripen; Afriyani, Dona (Jurnal Pembelajaran MIPA, 2014)
This research aim to know whether ability of mathematical conceptual understanding student which get a treatment model problem solving learning higher than which get a treatment conventional learning at VII grade in SMPN 1 Batusangkar. This kind of research is a quasi experiment with device is Randomized Control Group Only Design. Data ability of mathematical conceptual understanding obtained from final test. Hypothesis tested with MINITAB Program one way t-test. The result of this research is ability of mathematical conceptual understanding student mean experiment class 78.76, control class 68.35. Hypothesis test P-value = 0.0000, so that hypothesis this research accepted. Concluding that ability of mathematical conceptual understanding student which get a treatment model problem solving learning higher than which get a treatment conventional learning.Key words: Model Problem Solving learning, ability of mathematical conceptual understanding